Рrincipaltrends of the USA pedagogical thoughts development and their impact on vocational and tertiary education content - Ponomarova, O. I.; Kovalova, A. V. (Problems of Engineer-Pedagogical Education, 2018)
The article deals with some principal theoretical trends of further USA pedagogical ideas development.The new tendencies of pedagogical education content development are outlined, different concepts of American experts in this sphere are analyzed, ways of quality education improvement are regarded. It is stated that the whole period of the USpedagogical theory development has been under the influence of pragmatic, cognitive, technical and humanistic ideas which still have different approaches to education objectives and content as well as to various teaching techniques application. The requirements for specific professional skills were determined by different historical periods and depended on society economic development and its needs for manual and intellectual workers. The concept of people’s inherent intellectual abilities was analyzed, the demand for education division into “elite’ and that for “common people” was criticized.The tendency of the US quality education improvement is outlined.